Break-through : a sure-fire guide to realizing your potential, pushing through limitations, and achieving things you didn't know were possible - Nurse, David (John Wiley & Sons, Inc., 2022)
Deliver innovative results like clockwork with this repeatable formula for creativity-on-demand Have you ever sat down at your desk with an impossible deadline or an insurmountable obstacle staring you directly in the face and an expectation that you'll come up with a groundbreaking idea and solution? In Breakthrough, you'll find a powerful framework for bringing innovation and creativity to the surface not just once, but on a regular, daily basis. In Breakthrough, bestselling author, acclaimed speaker, and life optimization coach David Nurse provides an actionable and clearly organized structure for maximizing your breakthrough ideas. Breakthrough outlines easy-to-follow steps for outperforming your potential: An accessible blueprint--backed by scientific data and years of case studies with the top athletes, entrepreneurial minds, and leaders throughout the world--to unlocking your creative potential Conclusive proof that busts the myths of the lone genius, unpredictable 'a-ha' lightbulb moments, and little happy accidents Ways to promote an environment and mindset in which groundbreaking new ideas can flow and occur naturally and seamlessly based on a repeatable formula A must-read for any athlete, manager, executive, or parent tasked with delivering dynamic results in a flash, Breakthrough also belongs on the bookshelves of product design professionals, marketers, and other creative types who seek to consistently exceed expectations. Breakthrough is not about going from good to great; it's about going from great to outstanding!.